Sudden death among us - Quesada L., Fortunato (1919)
Fifty cases of sudden deaths with autopsies, I have the honor to submit to the Faculty and we have collected during the year and a half in the morgue in the capital, have been classified into four groups and an appendix considering its physio-pathology .